MATERIALISME DAN ISLAM - Willy Ramadan; Fitriah Fitriah (Postgraduate State Islamic Institute (IAIN) Metro, 2022)
The materialists tried to convince others that the cause of the growth and prevalence of materialism during the 18th and 19th centuries was the emergence of scientific theories and that it was the spread of science and technology that resulted in humanity being attracted in that direction. Muthahhari rejected this view. The growth of science or education has nothing to do with materialism. Materialism took the form of a school of thought during the eighteenth and nineteenth centuries. It was then that materialist ideas took the form of ideologies and many embraced them eagerly.